Female images of goddesses and heroines within the macro-concept HUMAN (on the material of Theocritus’ Idylls) - Івашків-Ващук, Орислава Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Women’s characters of Aphrodite, Helena, Berenice and Alcmene of the idylls of Theocritus, a prominent Greek poet of the Hellenistic period, are analyzed in the context of the macro-concept HUMAN. Such a research plays a great role in the study of the author’s idiostyle and his conceptual system. In the representation of the poet a woman can be a mother and a wife (Gorgo and Praxinoa from the XV idyll, Alcmene from the XXIV idyll), an unlucky, betrayed lover (Simaetha from II idyll), a naive shepherdess of goats (girl from the XXVII idyll), a proud nymph (Galatea from the XI idyll), a noble princess (Berenice from the XVII idyll), a demonstrative wife and crafter (Helena from the XVIII idyll) and others like that.In the questions of the study of the macro-concept of the HUMAN in the system of the ancient Greek language in general and on the material of Theocritus’ Idylls the human sphere should be considered in three segments: biological, spiritual and social.The dominant female image in the Theocritus’ idylls is the image of the goddess Aphrodite, whose characteristics can be found in almost every idyll. The images of heroines Helena, Berenice, and Alcmene are also important. These images have been analyzed in the context of the macro-concept HUMAN in more details. The lexical and stylistic displays of these images have been studied in particular. It is noted that the image of Aphrodite is cross-cutting for all idylls and has both positive and negative characteristics. Instead, the images of the heroines of Helena, Berenice and Alcmene are mostly realized in one of the idylls and are presented too ideally.